2022
DOI: 10.1101/2022.07.26.501656
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Honokiol inhibits SARS-CoV-2 replication in cell culture

Abstract: SARS-CoV-2 emerged in 2019 and since its global spread has caused the death of over 6 million people. There are currently few antiviral options for treatment of COVID-19. Repurposing of known drugs can be a fast route to obtain molecules that inhibit viral infection and/or modulate pathogenic host responses. Honokiol is a small molecule from Magnolia trees, for which several biological effects have been reported, including anticancer and anti-inflammatory activity. Honokiol has also been shown to inhibit sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Notably, honokiol protected VeroE6 cells from the SARS-CoV-2 infection with an EC50 value of 7.8 µM, decreasing the viral RNA copies and viral titers. Further investigations showed that honokiol inhibited SARS-CoV-2 replication, and they also suggested that honokiol is also active against many variants of SARS-CoV-2, including the Omicron variant and other human coronaviruses [ 109 ].…”
Section: Can Plant Products Overcome the Burden Of Sars-cov-2?mentioning
confidence: 99%
“…Notably, honokiol protected VeroE6 cells from the SARS-CoV-2 infection with an EC50 value of 7.8 µM, decreasing the viral RNA copies and viral titers. Further investigations showed that honokiol inhibited SARS-CoV-2 replication, and they also suggested that honokiol is also active against many variants of SARS-CoV-2, including the Omicron variant and other human coronaviruses [ 109 ].…”
Section: Can Plant Products Overcome the Burden Of Sars-cov-2?mentioning
confidence: 99%